Respuestas

¡La mejor respuesta!
  • Usuario de Brainly
2013-03-30T20:58:00+01:00

3x+5=6+x+5

3x - x = 6 + 5- 5

2x = 6

x = 6/2

x = 3

 

-4x+5=-7x-3+2x+10

-4x + 7x - 2x = - 3 + 10 - 5

1x = 2

x = 2

 

3x-2=2x+2

3x - 2x = 2 + 2

x =4

 

15-3x=8x-7

15 +7 = 8x + 3x

22 = 11x

22/11 = x

2 =x

 

 

4x+6=3x+12-x

4x - 3x + x = 12 - 6

2x = 6

x = 6/2

x= 3

 

 

5x-8x+x=7x-10+x

5x - 8x - 7x - x +x = - 10

- 10x = - 10

x = - 10 / - 10

x = 1

 

 

espero que te sirva, salu2!!!

 

 

2013-03-30T21:01:26+01:00

3x+5=6+x+5

3x - x = 6 + 5- 5

2x = 6

x = 6/2

x = 3

 

-4x+5=-7x-3+2x+10

-4x + 7x - 2x = - 3 + 10 - 5

1x = 2

x = 2

 

3x-2=2x+2

3x - 2x = 2 + 2

x =4

 

15-3x=8x-7

15 +7 = 8x + 3x

22 = 11x

22/11 = x

2 =x

 

 

4x+6=3x+12-x

4x - 3x + x = 12 - 6

2x = 6

x = 6/2

x= 3

 

 

5x-8x+x=7x-10+x

5x - 8x - 7x - x +x = - 10

- 10x = - 10

x = - 10 / - 10

x = 1

 

 

espero poderte ayudar